คุณแก้ปัญหาอย่างไร (1 + 2y) / (y-4) = (4y ^ 2 + 5y) / (2y ^ 2-7y-4)?

คุณแก้ปัญหาอย่างไร (1 + 2y) / (y-4) = (4y ^ 2 + 5y) / (2y ^ 2-7y-4)?
Anonim

# (1 + 2y) / (y-4) = (4Y ^ 2 + 5Y) / (2y ^ 2-7y-4) #

  • Factorize ด้านขวา:

# (4Y ^ 2 + 5Y) / สี (สีแดง) (2y ^ 2-8y + Y-4) #

# (4Y ^ 2 + 5Y) / สี (สีแดง) (2y (y-4) 1 (y-4) #

# = (4Y ^ 2 + 5Y) / (1 + 2y) (y-4) #

  • ใช้สมการเริ่มต้น:

# (1 + 2y) / สี (สีแดง) ยกเลิก (y-4) = (4Y ^ 2 + 5Y) / (1 + 2y) สี (สีแดง) ยกเลิก ((y-4) #

  • ข้ามคูณ

#COLOR (สีแดง) (1 + 2y) ^ 2 = 4Y ^ 2 + 5Y #

โดยการขยายตัว: # -> (A + B) ^ 2 = a ^ 2 + 2AB + B ^ 2 #

#COLOR (สีแดง) 1 + 4Y + ยกเลิก (4Y ^ 2) = ยกเลิก (4Y ^ 2) + 5Y #

ตอบ

# การ y = 1 #

ไปดูกัน: